Multikultural : Wacana Pendidikan Islam Yang Belum Baku - M.Agus Kurniawan (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Education aimed at shaping attitudes and behavior towards the civilized man. An education system that only emphasizes the transfer of knowledge, making education is no longer meaningful and a positive effect on learners. Education is not touching the side of humanism that develops an attitude of pluralism as a foundation of multiculturalism‟s thought. Model of religious education would only create only godly individually. Understanding multiculturalism has become a commodity in politics that will continue to roll in the realm of national education including Islamic religious education which is an integral part of the national education system. The government‟s policy regarding the application of curriculum which necessitates the provision of education oriented to potential of regional and local cultural values. This policy can not be separated from the awareness of the figures and leaders of this country that the Indonesian nation is very diverse and heterogeneous. Therefore, it is impossible to build this country withot considering of the values of plurality and multicultural in society